The trustwothly on busines | الأمانة في المجال التجاري - Ahmaddin Ahmad Tohar (Al-Zahra : Journal for Islamic and Arabic Studies, 2008)
Commerce is one of income generating activities. It issubjected to any act of cheating and fabrication.Trustworthy is extremely needed by any entrepreneuror businessman in dealing with his commerce. Thesuccess of commerce is not only measured by worldlygain but more by hereafter profit. Thus the commercemust be halal (allowed) and based on rida (sincere) intransaction. The trustworthy commerce will givebarakah (blessing) and multiple profit.